Effect of the Addition of Protected Soybean Groats on the Digestibility of Complete Feed for Thin-tailed Sheep - Riyanto, Joko; Ikhsan, Muh; Delji, Roby; Nissa, Nasta ‘Ainun (Jurnal Ilmu-Ilmu Peternakan, 2024)
This study aims to investigate the effects of the use of complete feed containing different protected soybean groats on the digestibility of dry matter (DM), organic matter (OM), crude protein (CP), and total digestible nutrient (TDN) contents in male thin-tailed sheep. The materials used in this study were 15 male, thin-tailed sheep with an average initial body weight of 23.43 ± 1.40 kg. The research design used was a completely randomized design (CRD) with 3 treatments and 5 replicates. The treatments in this study were as follows: T1 = 100% complete feed, T2 = 90% complete feed + 10% protected soybean groats, and T3 = 80% complete feed + 20% protected soybean groats. The data were analysed via analysis of variance. The results of the analysis of variance revealed that the use of complete feed containing protected soybean groats had no significant effect (P > 0.05) on the consumption of dry matter, organic matter, or crude protein or on the digestibility of dry matter, organic matter, or crude protein. In conclusion, the use of complete feed containing protected soybean groats has no effect on the digestibility of dry matter (DM), organic matter (OM), crude protein (CP), or total digestibility of nutrients (TDN) in thin-tailed sheep.